Low cost shaped beam synthesis for semi‐smart base station antennas. Issue 1 (1st January 2016) - Chen, Zhijiao; Parini, Clive
Abstract : The authors present a low cost shaped beam synthesis method for semi‐smart base station antennas. Compared with the conventional array synthesis for smart antenna applications, the proposed circular/conformal array shaped beam synthesis for semi‐smart antenna has much lower system complexity and instrumentation implementation cost. This is because only few elements are involved and the circular array factor is simplified for coarse granularity beam. Adding to this, a fast quasi‐Newton method is used by the linear/conformal array for the beam optimisation. By coding the shaped beam synthesis methodology in C/C++, the shaped beam synthesis for 12‐element circular array is implemented for the semi‐smart macrocell, showing its advantages of low‐consumed time and stable mean square errors. Furthermore, a semi‐smart sectored picocell has been designed with 4‐element conformal array, which was demonstrated to be superior to the linear one by avoiding the blind angle, exhibiting better accuracy and less consumed processing time.